Geriatric nutritional risk index and body composition dictate the prognosis of elderly patients with intrahepatic cholangiocarcinoma - Wang, Sheng; Cheng, Luo; Dou, Lei; Kuang, Yuanli; Huang, Yang; Wen, Tao; Xiang, Lei; Xie, Wenyuan; Zhang, Cheng; Li, Dewei; Li, Hui (Frontiers in Nutrition, 2025)
Background and aimsMalnutrition is a well-recognized predictor of poor prognosis in malignancies. Recent studies suggest that the geriatric nutritional risk index (GNRI) is a more accurate determinant of prognosis in elderly patients than conventional body mass index (BMI). This study aimed to evaluate the GNRI and body composition parameters in elderly patients with intrahepatic cholangiocarcinoma (ICC) and assess their prognostic impact on long-term outcomes.MethodsA total of 157 elderly ICC patients (aged ≥65 years) who underwent radical resection between 2009 and 2018 were retrospectively analyzed. Skeletal muscle index (SMI), muscle attenuation (MA), visceral adipose tissue index (VATI), subcutaneous adipose tissue index (SATI), and visceral-to-subcutaneous fat ratio (VSR) were quantified using computed tomography. Prognostic analyses were conducted using the Kaplan–Meier method, with adjustments using inverse probability weighting. A nomogram based on multivariate Cox regression was constructed and internally validated, comparing its prognostic accuracy with the TNM staging system.ResultsAmong the body composition parameters, low SMI (sarcopenia, 56.1%), high VSR (visceral adiposity, 54.8%), and low MA (intramuscular fat deposition, 50.3%) were significantly associated with overall survival (OS) and recurrence-free survival (RFS) (all p < 0.05). Low GNRI was also a strong predictor of poor prognosis (p < 0.001). Multivariate analysis identified low GNRI (p = 0.009), sarcopenia (p = 0.020), visceral adiposity (p = 0.033), and intramuscular fat deposition (p = 0.036) as independent prognostic factors for OS and RFS. The nomogram, incorporating GNRI, SMI, VSR, MA, microvascular invasion (MVI), CA19-9 levels, and lymph node invasion, demonstrated superior prognostic performance compared to the TNM stage, with a C-index of 0.734 (OS) and 0.704 (RFS) and an AUC of 0.809 (OS) and 0.815 (RFS).ConclusionGNRI, sarcopenia, IMF deposition, and visceral adiposity independently predict mortality and tumor recurrence in elderly ICC patients. Body composition is a major determinant of prognosis in patients with ICC. Our nomogram based on body composition reveals superior prognostic efficacy over TNM stages.